Kompetensi Guru Dalam Perencanaan Pembelajaran Di UPT SPF SDN 107399 Bandar Khalipah - Masriana Masriana; Nurul Hasanah; Nur Arifa Hasanah; Zumiati Syarah (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
In the learning process, planning and organizing learning is a teacher’s mandatory task so that the expected learningg is in accordance with the learning that will occur. This research seeks to describe teacher’s abilities in preparing learning plans at SDN 107399 Bandar Khalipah. The approach used in this research is qualitative in the type of descriptive reasearch. The data for this reseacrh comes from sources who have been interviewed, while the data souces are class teachers at SDN 107399 Bandar Khalipah. The data collection process was carried out using checklist techniques, interviews and documentation. The interview technique used was a semi structured interview. In carring ut the documentation, the researcher reviewed 10 syllabi and lesson plans that had been prepared by the class teacher at SDN 107399 Bandar Khalipah. So that the interview data can be trusted, researchers use tools in the form of writing instruments and other electronic media. Based on data analysis, the findings of this research can be stated as follows. First, when we are going to prepare a learning plan,the teacher will use the syllabus as a guide in designing the learning implementation plan. The teacher must have 4 teacher competencies, namely the ability to develop and prepare learning implementation Plans that are in accordance with the curriculum, applies. The conclusion of this research is that the teacher at SDN 107399 Bandar Khalipah in planning learning can be seen from the way the teacher plans and prepares lesson plans that are inaccordance with the Merdeka Belajar curriculum and by showing competence in planning learning at school.